Giant Left Atrium in an Infant with Anomalous Origin of Left Coronary Artery from Pulmonary Artery - Singh, Damandeep; Mukherjee, Aprateem; Kumar, Sanjeev; Gupta, Saurabh Kumar (Indian Journal of Radiology and Imaging, 2024)
Anomalous origin of the left coronary artery (ALCAPA) from the pulmonary artery is a rare congenital anomaly with coronary steal and myocardial ischemia. The left ventricular dilatation leads to mitral regurgitation causing left atrial enlargement. We report a rare case of giant left atrium in an infant with ALCAPA-mediated secondary mitral regurgitation, which has been hitherto unreported.
Keywords: ALCAPA; congenital heart disease; giant left atrium